2015
DOI: 10.1371/journal.pone.0136420
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated Enterovirus 71 Vaccine Produced by 200-L Scale Serum-Free Microcarrier Bioreactor System Provides Cross-Protective Efficacy in Human SCARB2 Transgenic Mouse

Abstract: Epidemics and outbreaks caused by infections of several subgenotypes of EV71 and other serotypes of coxsackie A viruses have raised serious public health concerns in the Asia-Pacific region. These concerns highlight the urgent need to develop a scalable manufacturing platform for producing an effective and sufficient quantity of vaccines against deadly enteroviruses. In this report, we present a platform for the large-scale production of a vaccine based on the inactivated EV71(E59-B4) virus. The viruses were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Moreover, the VP1–104 residue encoded two different amino acids (Asn and Asp) in the wild-type EV-V, but these were mutated into the unique residue Asn in EV-R (Table 1 ). We sequenced another genotype, B4 of EV71 E59, which has been used as a vaccine strain 48 , and found that the VP1–145 residue encoding Gly remained the same after passage in RD and Vero cells. These phenomena have been observed in previous studies; substitution of residue 145 from E to G while passage of EV71 in RD was observed 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the VP1–104 residue encoded two different amino acids (Asn and Asp) in the wild-type EV-V, but these were mutated into the unique residue Asn in EV-R (Table 1 ). We sequenced another genotype, B4 of EV71 E59, which has been used as a vaccine strain 48 , and found that the VP1–145 residue encoding Gly remained the same after passage in RD and Vero cells. These phenomena have been observed in previous studies; substitution of residue 145 from E to G while passage of EV71 in RD was observed 49 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with EV71 replication in natural systems, the production of EV71 virus vaccine in bioreactors with a suspended microcarrier system yields both FP and EP particles [20]. A previous mouse vaccination study showed that FPs derived from the B4(E59) strain are more potent antigens than EPs and confer superior immunogenic efficacy in the neutralization of homologous virus [21].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, numerous studies have focused on vaccine development in the past decade [45][46][47][48][49], and inactivated EV71 vaccines, providing an invaluable gift for children, were developed successfully [11,12,50]. Several EV71 genotypes such as C4a, B5, C2 were circulating in the Asia-Pacific Region in the past decade and EV71 genotypes might be the key factor to affect vaccine cross-neutralization [51][52][53][54][55]. Hence, it would be further investigated whether EV71 vaccines developed using a single EV71 strain could provide strong cross-protection against other EV71 strains.…”
Section: Discussionmentioning
confidence: 99%